Do Listed Banks have Higher Operating Efficiency and Output Efficiency?1. (3rd September 2018) - Li, Zeguang; Hou, Keqiang; Cottrell, Simon
Abstract : This paper investigates the efficiency and productivity of listed and non‐listed banks in China by using the meta‐frontier and GMMPI methods. We find that the improvement in productivity of listed and non‐listed banks is mainly due to changes in technological efficiency. The difference between them is that the improvement of productivity of listed banks presents a typical technology‐driven feature, and changes in scale efficiency negatively affect productivity. The productivity of non‐listed banks shows scale efficiency driving features. The meta‐frontier efficiency of listed banks is significantly higher than the others. After decomposing the technology gap ratio, we find that the current production technology of the listed banks is closer to the potential production technology frontiers, and there is space for the non‐listed banks to improve their efficiency. Besides, the gaps between the true extent and the potential technological frontiers of both listed banks and non‐listed banks have converged.